2020
DOI: 10.3390/su12083102
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Algorithm for Embodied Energy Optimisation of Steel-Concrete Composite Beams

Abstract: The optimisation of structural performance is acknowledged as a means of obtaining sustainable structural designs. A minimisation of embodied energy of construction materials is a key component in the delivery of sustainable future designs. This study attempts to understand the relationship between embodied energy and structural form of composite floor plates for tall buildings, and how this form can be optimised to minimise embodied energy. As a search method based upon the principles of genetics and natural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The concept of a stress amplitude-fatigue frequency curve was first proposed by August Wohler [14]. The standard was utilized to categorize the various fatigue strengths of welded joints, and the subsequent fatigue design comprises keeping the nominal stress amplitude of the structure within an appropriate range [15]. Keeping the stress amplitude below the point where microcracks can propagate is the key to successfully imposing a stress threshold.. Because of its exceptional performance and convenient construction, the steel-concrete composite structure is frequently used in the construction of bridges [16].…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…The concept of a stress amplitude-fatigue frequency curve was first proposed by August Wohler [14]. The standard was utilized to categorize the various fatigue strengths of welded joints, and the subsequent fatigue design comprises keeping the nominal stress amplitude of the structure within an appropriate range [15]. Keeping the stress amplitude below the point where microcracks can propagate is the key to successfully imposing a stress threshold.. Because of its exceptional performance and convenient construction, the steel-concrete composite structure is frequently used in the construction of bridges [16].…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…In addition to the papers presented above, other studies have addressed the issue of optimizing energy cost (or energy consumption) through genetic algorithms. Pillai et al [25] present a method to reduce power consumption in a multi-processor system. Here, task planning (program sequences) must be performed, to keep processors at the point of operation that involves the lowest power consumption for as long as possible.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In this context, a concept that has been studied is embodied energy in materials of buildings [1]. In Whitworth and Tsavdaridis [2,3], optimization studies were presented in Steel-Concrete composite beams with the objective of presenting sustainable structural designs by minimizing the embodied energy. The study showed that it is possible to reduce the embodied energy of these structural systems, considering the design recommendations of Eurocode 4 [4].…”
Section: Introductionmentioning
confidence: 99%